History and Experience of Central Sulawesi Communities Facing the Influenza Pandemic 1918—1920 - Adi Setiawan; Nurhalisa Nurhalisa; Nanda Pratiwi; Haliadi Haliadi (MOZAIK HUMANIORA, 2022)
This study aims not only to explain the handling efforts, but also to analyze the experiences and collective memories of the people of Central Sulawesi when they faced influenza pandemic in 1918—1920. A century ago, before the Covid-19 pandemic broke out in 2020, an influenza pandemic had plagued the people of Central Sulawesi. Unfortunately, there was very little literature describing these cases. Hence, historical method is used together with certain sources, such as books, journal articles, newspapers, archives, and interviews related with the issue. The results then show that the influenza pandemic in Central Sulawesi began in late 1918 and lasted until the early 1920s. The colonial government at that time tended to be late in dealing with this pandemic. As a result, treatment efforts at the local level were mostly driven by missionaries and colonial officers who had been equipped with the knowledge of modern medicine for tropical diseases. In addition, certain tactics were carried out by several local communities including migration, self-quarantine, and prevention efforts by implementing a hygiene lifestyle and providing food barns to prevent famine during a pandemic. In conclusion, efforts to deal with the influenza pandemic in Central Sulawesi were very limited due to the lack of health facilities and the number of medical personnel, so it was not sufficient to overcome the disease and its spread. However, people's experiences with influenza at that time were stored quite well in their collective memory. Therefore, some of these experiences related to local knowledge can be used as lessons to deal with the current Covid-19 pandemic.